A Study on Accelerated Thermal Aging of High Modulus Carbon/Epoxy Composite Material - Ju Min Kyung; Choi Ji-Ung; Lee Ho-Sung (MATEC Web of Conferences, 2015)
Composite materials have been used increasingly for various space applications due to the favorable characteristic of high modulus to density ratio and potential for near-zero coefficient of thermal expansion. In composite system, depending on the orientation of fibers, strength and stiffness can be changed so that the optimum structure can be accomplished. This is because the coefficient of thermal expansion (CTE) of carbon fibers is negative. For spacecraft and orbiting space structure, which are thermally cycled by moving through the earth' shadow for at least 5 years, it is necessary to investigate the change of properties of the material over time. In this study, thermal aging of epoxy matrix/high modulus carbon fiber composite materials are accelerated to predict the long term creep property. Specimens are tested at various temperatures of 100~140°C with dynamic mechanical analysis to obtain creep compliances that are functions of time and temperature. Using Time Temperature Superposition method, creep compliance curves at each temperature are shifted to the reference temperature by shift factor and a master curve is generated at the reference temperature. This information is useful to predict the long term thermal aging of high modulus composite material for spacecraft application.